Exploring the Effects of Tomatidine ((3β, 5α, 22β, and 25β)-Spirosolan-3-ol) on Voltage-gated Na+ currents: Insights Into Its Ionic Mechanisms of Action on Current Magnitude, Gating, and Frequency Dependence - Tso-Lin Lin; Edmund Cheung So; Sheng-Nan Wu (Journal of Physiological Investigation)
Tomatidine, a major tomato glycoalkaloid, is effective for the prevention of skeletal muscle wasting and enhancing mitophagy. However, its effects on transmembrane ionic currents are not well explored. In this study, we explored the interactions between tomatidine and Na+ current. GH3 or Neuro-2a cells were used for recording the ion currents employing modified patch-clamp technique under whole-cell configuration. Tomatidine increased both the peak, (transient Na+ current [INa (T)]) and sustained (late Na+ current [INa (L)]) components of voltage-gated Na+ current (INa) in a concentration-dependent manner, with the concentration required for 50% stimulation values of 43.3 μM and 3.1 μM, respectively. The steady-state current-voltage relationship of INa (T) remained unchanged; however, the steady-state inactivation curve of INa (T) in the presence of 3 μM tomatidine was shifted to less depolarized potential by around 6 mV. Tomatidine enhanced the window INa (window Na+ current [INa (W)]), which were attenuated by the ranolazine (Ran) and carbamazepine (CBZ). During a train of depolarizing pulses, tomatidine slowed the exponential decay of INa (T), and this effect was reversed by Ran or dapagliflozin. Tomatidine increased both fast and slow recovery time constants from INa (T) block, affecting the recovery time course. Tomatidine increased the amplitude of persistent Na+ current in response to a sinusoidal waveform. In neuro-2a cells, tomatidine increased INa (T) amplitude and slowed its inactivation, with this effect being attenuated by Ran or CBZ. In conclusion, tomatidine enhanced magnitude and modified its gating behaviors.